Utilisation of the partogram among nurses and midwives in selected health facilities in the Eastern Province of Rwanda - Oliva Bazirete; Nomafrench Mbombo; Oluyinka Adejumo (AOSIS, 2017)
Background: Maternal mortality continues to be a global burden, with more than 200 million women becoming pregnant each year and a large number dying as a result of complications of pregnancy or childbirth. The World Health Organisation has recommended use of the partogram to monitor labour and delivery in order to improve healthcare and reduce maternal and foetal mortality rates. Objective: This study described factors affecting utilisation of the partogram among nurses and midwives in selected health facilities of Rwanda. Method: A descriptive quantitative and cross-sectional research design was used. The population comprised 131 nurses and midwives providing obstetric care in 15 health institutions (1 hospital and 14 health centres). Data collection was through a self-administered questionnaire, and a pre-test of the data collection instrument was carried out to enhance validity and reliability. The Statistical Package for Social Sciences (version 21) was used to capture and analyse data. Ethical clearance was obtained from the University of the Western Cape (Republic of South Africa) and from the Institutional Review Board of Kigali Health Institute (Rwanda). Patricia Benner's model of nursing practice was used to guide the study. Results: It was found that 36.6% of nurses and midwives did not receive any in-service training on how to manage women in labour. Despite fair knowledge of the partogram among nurses and midwives in this study, only 41.22% reported having used the partogram properly, while 58.78% reported not having done so. Conclusion: Nurses' and midwives' years of professional experience and training in managing pregnant women in labour were found to be predictors of the likelihood of proper use of the partogram. In-service training of obstetric caregivers in the Eastern Province of Rwanda is recommended to improve use of the partogram while managing women in labour.